Contribution of Congenital Heart Disorders Associated With Copy Number Variants in Mediating Risk for Brain Developmental Disorders: Evidence From 20-Year Retrospective Cohort Study - Dowden, Luke; Tucker, David; Morgan, Sian; Uzun, Orhan; Syed, Yasir Ahmed (Frontiers in Cardiovascular Medicine, 2021)
Rare pathogenic copy number variants (CNVs) are genetic rearrangements that has been associated with increased risk for congenital heart disorders (CHDs). However, their association towards atypical brain development leading to neurodevelopmental disorders (NDDs) in presence of CHDs remains unclear. We attempted to explore this association, by establishing the prevalence and burden of CNVs associated with CHD in Welsh population and by studying the relationship of rare CNVs associated with CHDs, in mediating the risk of NDDs. Towards this goal, we analysed the data from Congenital Anomaly Register for Wales (CARIS), referred from hospitals in Wales, during 1998-2018, which included 1113 subjects. A total of 785 subjects were included in the study following application of exclusion criteria and a total of 28 rare CNVs associated with CHD were analysed. Findings from this cohort study identifies 22q11.2 deletion to be the most prominent CNVs across the cohort. Our data demonstrates that, the survival rate of the cohort over a three-year period was 99.9%, and mortality fell significantly between one year and two years, and between two years and three years (F1,27 = 10, p = 0.0027; F1,27 = 5.8, p = 0.0222). Importantly, the data set revealed a positive correlation between the incidence of congenital heart disease and the incidence of neurodevelopmental abnormalities in patients with CNVs across whole cohort (95% CI [0.4062, 0.8449], p < 0.0001, r = 0.6829). Additionally, we identified significant CNVs that results in co-morbidity of CHD and NDD and show that septal defects and global developmental delay to be major congenital defects. Further research should identify common molecular mechanism leading to phenotypic comorbidity of CHDs and NDDs, arising from common CNV, which can have implication for improving risk classification, for foetal neuroprotection strategies in affected children and in precision medicine.